ANALISIS PENGARUH KESELAMATAN, KESEHATAN, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN BAGIAN WORKSHOP (STUDI KASUS: PT XYZ) - Liperda, Rahmad Inca; Hernawati, Theodora Rinda (Universitas Majalengka, 2023)
This research was carried out with the aim of evaluating the impact of the working environment, health and safety at work on the performance of workers in the PT XYZ Workshop division. I thought about using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS), and SMARTPLS software uses Least Squares handling for variation. The analysis results show that occupational safety and health factors have a significant influence on employees’ work performance and motivation, while work environmental factors do not have a significant impact on performance. And employee work motivation. Furthermore, work motivation has no effect on employee performance, so it does not play a mediating role in the relationship between safety, health and the work environment and employee performance.